PEMBERESAN HARTA PAILIT PT. ASURANSI BUMI ASIH JAYA DEBITOR KEPADA KREDITOR CABANG PEKANBARU - Rio Rizky Ramadhan; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The bankruptcy of PT. Asuransi Bumi Asih Jaya Pekanbaru branch causes uncertainty about the status of insurance claims as debt and the position of creditors for the bankruptcy of this company. The number of Bumi Asih Jaya insurance policy holders who have made claims and who have been verified by the curatorial team are 500 policyholders. The curatorial team that has been formed consists of five. Bumi Asih Jaya is recorded as still having a claim debt of Rp. 85.6 billion. The demands of this Bumi Asih Jaya insurance policy holder are that the customer's money can be returnedThis type of legal research is juridical sociological, which in this research, is carried out directly to the field to collect primary data, and uses descriptive methods. Meanwhile, if viewed from the nature of this research is descriptive.The results of this study are the settlement of the bankruptcy assets of PT. Asuransi Bumi Asih Jaya debtor to creditors of the Pekanbaru branch, namely PT Bumi Asih Jaya, has had its business license revoked by OJK through the Decree of the OJK Board of Commissioners Number: Kep 112 / D.05 / 2013 dated 18 October 2013, while the company was declared bankrupt by the court on 28 August 2015. Regarding the settlement of bankruptcy assets, which are the company's assets, which will then be used to fulfill the company's obligations to creditors is the authority of the curator. The responsibility of PT Bumi Asih Jaya to creditors for bankruptcy filed by the debtor is to hand over the company's assets to the curator. The curator who cleared the bankruptcy estate from PT Bumi Asih and also took care of credit repayments for creditors who made claims.Keywords: Bankruptcy Assets Settlement, Debtors, Creditors